Genetic variation in a haplotype block spanningIDE influences Alzheimer disease - Jonathan A. Prince; Lars Feuk; Harvest F. Gu; Boo Johansson; Margaret Gatz; Kaj Blennow; Anthony J. Brookes (2003)
Linkage studies have identified a large (>60-Mb) region on chromosome 10q that segregates with Alzheimer Disease (AD). Within the region, the gene for insulin degrading enzyme (IDE) represents a notable biological candidate given that it degrades amyloid β-protein (one of the major constituents of senile plaques) and the intracellular amyloid precursor protein (APP) domain released by γ-secretase processing. We have used a single nucleotide polymorphism (SNP) genetic association strategy to investigate AD in relation to a 480-kb region encompassing IDE. A 276-kb linkage disequilibrium block was revealed that spans three genes (IDE, KNSL1, and HHEX). Assessing this block in several independent sets of case-control materials (early- and late-onset AD) and focusing also upon quantitative measures that are pertinent to AD diagnosis and severity (MMSE scores, microtubule-associated protein Tau [MAPT] levels in CSF, degree of brain pathology, and age-at-onset) produced extensive evidence for significant AD association. Signals (p-values ranging from 0.05 to <1×10−9) were generally stronger when examining haplotypes rather than individual SNPs, and quantitative trait tests most uniformly revealed the detected associations. Consistent risk alleles and haplotypes were apparent across the study, with effects in some cases as large as that of the ϵ4 allele of APOE. A subsequent mutation screen of exons in all three suspect genes provided no evidence for common causative mutations. These results provide substantial evidence that genetic variation within or extremely close to IDE impacts both disease risk and traits related to the severity of AD. Hum Mutat 22:363–371, 2003. © 2003 Wiley-Liss, Inc.